2016
DOI: 10.1007/978-3-319-31248-4_3
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and their Metabolites: Potential Implications for the Host Epigenome

Abstract: The gut microbiota represents a metabolically active biomass of up to 2 kg in adult humans. Microbiota-derived molecules significantly contribute to the host metabolism. Large amounts of bacterial metabolites are taken up by the host and are subsequently utilized by the human body. For instance, short chain fatty acids produced by the gut microbiota are a major energy source of humans.It is widely accepted that microbiota-derived metabolites are used as fuel for beta-oxidation (short chain fatty acids) and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 78 publications
0
34
0
1
Order By: Relevance
“…However, long-lasting changes in the epigenetic make up of the host in response to alterations of the microbiome extend even beyond the immune system to affect, e.g., metabolism, and connects the theme of this review to the developmental origin of health and disease (126). Specifically, this includes bacterial products that function as substrates for one-carbon metabolism (e.g., vitamins B2, B6, B9, and B12), and substrates for epigenetic modification (e.g., vitamin B7 for biotinylation and vitamin B5 for acetylation), or metabolites that interfere with the host epigenetic machinery (e.g., SCFA-mediated histone deacetylase inhibition) (127). Furthermore, pre- and early postnatal life is thought to be critical window for epigenetic modification specifically because growth and cell division are then at their highest rate.…”
Section: Resultsmentioning
confidence: 99%
“…However, long-lasting changes in the epigenetic make up of the host in response to alterations of the microbiome extend even beyond the immune system to affect, e.g., metabolism, and connects the theme of this review to the developmental origin of health and disease (126). Specifically, this includes bacterial products that function as substrates for one-carbon metabolism (e.g., vitamins B2, B6, B9, and B12), and substrates for epigenetic modification (e.g., vitamin B7 for biotinylation and vitamin B5 for acetylation), or metabolites that interfere with the host epigenetic machinery (e.g., SCFA-mediated histone deacetylase inhibition) (127). Furthermore, pre- and early postnatal life is thought to be critical window for epigenetic modification specifically because growth and cell division are then at their highest rate.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the capacity of gut microbes to induce a pro-carcinogenic inflammatory response [41][42][43]. The second is the production of secondary metabolites by gut microbes [44][45][46]. The ability of short chain fatty acids (SCFAs), hydrogen sulfide (H 2 S), secondary bile acids, and many other metabolites to impact the genome or epigenome of CECs, to alter rates of CRC progression, and to function as targets for CRC prevention or treatment is tremendously important and has thus been the topic of many recent reviews [47][48][49][50].…”
Section: Not Yet Identifiedmentioning
confidence: 99%
“…Recent studies have shown gut microbiota and their metabolites could affect the host epigenome [28], suggesting that MIMP may also regulate the expression of inflammatory cytokines in an epigenetic manner. Because histone acetylation is closely associated with gene activation, we measured the global acetylation level of histone H4 or H3 in CaCO-2 cells treated with PBS (control), LPS, the TLR4 antagonist or MIMP.…”
Section: Resultsmentioning
confidence: 99%